Combining Cetuximab and Immunotherapy for Treating MSS/pMMR Colorectal Cancer: Current Evidence and Challenges - Bo Pei PhD; Shixuan Peng MS; Weiwei Chen BS; Lin Lai MS; Fuxiang Zhou PhD (Technology in Cancer Research & Treatment)
Colorectal cancer (CRC) remains a formidable global health challenge, with the majority of patients exhibiting microsatellite stable (MSS) and proficient mismatch repair (pMMR) tumors that are largely unresponsive to immune checkpoint inhibitors (ICIs). The management of MSS/pMMR CRC remains a clinical challenge due to the intrinsic resistance to ICIs. The innovative strategy of combining cetuximab, an EGFR-targeting monoclonal antibody with immunomodulatory properties, offers a promising strategy to enhance the immunotherapeutic response in MSS/pMMR CRC. This combination therapy is rooted in the complementary therapeutic mechanisms of cetuximab and ICIs, which may synergistically improve overall response rates and durability of response. Although some preclinical and clinical data have suggested additional promising results, there are still some challenges and questions that need to be addressed. Further large-scale, randomized, phase III clinical trials are required to confirm the efficacy and safety of this combination therapy. The ongoing clinical trials evaluating the safety and efficacy of cetuximab-ICI combinations are eagerly anticipated to pave the way for a new era in personalized immunotherapy for MSS/pMMR CRC.